Organ donation and transplantation in the Russian Federation in 2019. 12th report from the Registry of the Russian Transplant Society - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов)
Objective: to monitor current trends and developments in organ donation and transplantation in the Russian Federation based on the 2019 data. Materials and methods. Heads of organ transplant centers were surveyed. Data obtained over years from federal subjects of the Russian Federation and from organ transplant centers in the country were analyzed and compared. Results. Based on data retrieved from the 2019 Registry, only 46 kidney, 31 liver and 17 heart transplant centers were functioning in Russia. In 2019, there were 6,878 potential recipients in the kidney transplant waitlist. This represents 13.7% of the 50,000 dialysis patients in the country. Donation activity in 2019 reached 5.0 per million population; multi-organ procurement rate was 71.6%; 2.9 organs on average were procured from one effective donor. In 2019, there were 10.0 kidney transplants per million population, 4.0 liver transplants per million population and 2.3 heart transplants per million people. Same year, the number of transplant surgeries performed in Russia rose 10.7% from the previous year. Moscow and Moscow Oblast alone have 13 functioning organ transplantation centers. They account for half of all kidney transplant surgeries and 70% of all liver and heart transplants performed in the country. Organ recipients in the Russian Federation have exceeded 16,000 in number. Conclusion. Organ transplantations in Russia keep on increasing – 10–15% per year. Donor and transplant programs are also becoming more effective and efficient. However, the demand for organ transplants far exceeds the current supply of available organs in the Russian Federation. Peculiarities of the development of organ donation and organ transplantation in Russia in 2019 were associated with some factors, such as structure and geographical location of transplant centers, waitlisting of patients, funding sources and amount, and management of donor and transplant programs. The national transplantation registry will be developed taking into account new monitoring and analysis challenges.